RHETORICAL MOVES IN THESIS INTRODUCTION WRITTEN BY ENGLISH MAJOR STUDENTS - Ulil Fitriyah (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims at investigating rhetorical pattern deployed by undergraduate students of English literature department in composing academic research introduction in their undergraduate thesis. By using CARS model (Swales, 2004), this study analyzed ten students’ Research Introductions (RI) written by low and high achievers. Five set of students’ RI written by high achievers was contrasted with five other sets of RI of their counterpart. This study is objected to investigate the rhetorical patterns employed differently by low and high achievers. The analysis reveals that both groups employed almost similar rhetorical pattern in writing theirRAI and they still wrestle in arranging the well-established paragraphs as well as occupying the moves in CARS rhetorical pattern. The result of the study also indicates that both high and low level students experienced similar problem in writing successful RAI in their thesis.